Local Wisdom as a Sustainable Strategy for Public Space Management in Makassar - Djufri, Djufri; Arifin, Ansar; Basir, Muhammad (Buletin Antropologi Indonesia, 2025)
This study aims to explore how the local wisdom of the Bugis-Makassar community can be integrated into sustainable public space management in Makassar. Using Lefebvre’s theory of the Production of Space, Harvey’s Right to the City, and the concept of cultural sustainability, the research positions public space as a social and political construct shaped by power relations and cultural meaning. The study adopts a qualitative ethnographic approach, with data collected through participant observation, in-depth interviews, and visual documentation in key public spaces including Losari Beach, Karebosi Field, and community-driven alleyways (Lorong Wisata). Findings reveal that urban modernization tends to marginalize local wisdom, exacerbating inequality and undermining social cohesion. However, grassroots initiatives rooted in cultural values such as siri’ na pacce and gotong royong show strong potential for inclusive and participatory revitalization. These findings contribute to spatial theory by integrating cultural dimensions into the concept of spatial production and offer practical strategies for equitable and culturally grounded urban planning.